ISOLATION, CHARACTERIZATION AND EXPRESSION ANALYSIS OF PUTATIVE DROUGHT RESPONSIVE EXPRESSED SEQUENCED TAGS FROM GOSSYPIUM ARBOREUM ROOTS - A. Jamal; 2; M. N. Shahid; B. Aftab; A. K. Johargy; M. S. Alshmemri; B. Rashid; T. Husnain (Journal of Animal and Plant Sciences, 2020)
Cotton is an important economic fibre crop. Seasonal water shortages and long term water deficit can effect cotton yield. Current study aimed to explore the cotton root transcriptome under drought stress. mRNA extracted from cotton roots subjected to osmotic stress treatment (5% gravimetric humidity) was used to construct cDNA library. Expressed sequence tags submitted to gene bank EST database (JK757087-JK757798) further annotated to predict the homology and function. Total 104 transcripts with an E-value less than 1e-33 revealed 82 (78.84%) known homologs and 22 (21.15%) with uncharacterized proteins. Gene ontology and KEGG analysis of these drought responsive ESTs elucidated their key role in biological regulation, molecular functions and cellular organelles. Expression pattern of 10 unigenes were validated by RT-qPCR in roots and leaves. These unigenes included WD repeat, FRIGIDA, peroxidase, E3 ubiquitin ligase, U-box domain, RNA binding, calcyclin binding, Glutathione S transferase, endochitinase and metallothionine like protein. cDNA library was successfully constructed from cotton roots and revealed several key drought responsive transcripts. Novel sequences identified in this study can be valuable resource for further exploration studies to exploit their role in genomics of drought responsive mechanism.
Keywords: Drought stress; Expressed Sequence Tags (EST); Homology; KEGG; Orthologs; qRT-PCR